Do urethral Escherichia coli cause abacterial cystitis?. Issue 2 (February 1983) - Walpita, P; Marsh, F P
Abstract : To determine whether Escherichia coli in or near the urethra caused symptoms of abacterial cystitis, the results of serial cultures from the vaginal introitus of 92 patients with recurrent cystitis were compared with symptoms at clinic visits when they were abacteriuric. Similar comparisons were made in 15 of these patients using cultures from the external urethral meatus and proximal urethra. E coli were grown from the vaginal introitus, urethral meatus and proximal urethra at 41, 66 and 26% of visits respectively. Overall they were not significantly more often isolated when patients had cystitis, and the serotype was unrelated to symptoms. E coli was cultured significantly more often from the introital swabs of symptomatic intermittently bacteriuric (IB) women than from symptomatic persistently non-bacteriuric (NB) patients; and more often from symptomatic than from asymptomatic IB patients, although this difference was not significant. These findings were consistent with previous suggestions that symptoms of apparently "abacterial" cystitis in IB patients are due to occult coliform infection. We found no direct evidence that E coli were the cause of symptoms in persistently non-bacteriuric women, or that urethral colonisation caused them. However E coli were isolated from the introitus of control women only half as often as from both intermittently bacteriuric and persistently non-bacteriuric patients.